2021
DOI: 10.1055/s-0040-1722647
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyocutaneous Free Fibula Flap Prevents Osteoradionecrosis and Osteomyelitis in Head and Neck Cancer Reconstruction

Abstract: Background Osteoradionecrosis (ORN) is one of the most severe complications of free fibula reconstruction after radiotherapy. The gold standard treatment of osteomyelitis involves extensive debridement, antibiotics, and sufficiently vascularized muscle flap coverage for better circulation. Therefore, we hypothesized that free fibula flap with muscle could decrease the risk of ORN. Methods This study consisted of 85 patients who underwent reconstruction with free fibula flap in head and neck cancer by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
4
1
1
Order By: Relevance
“…Eight (57%) of 14 patients with ORN were diagnosed at 5 years or longer after IMRT completion. Despite high reported rates of ORN in two prior studies specifically evaluating fibular free flaps (34%-47%), 18,19 the present findings found that mandibular reconstruction did not escalate risk of ORN. The incidence of ORN in reconstructed mandibles was 7.9%, which was slightly lower than that of native mandibles (9.4%), and the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Eight (57%) of 14 patients with ORN were diagnosed at 5 years or longer after IMRT completion. Despite high reported rates of ORN in two prior studies specifically evaluating fibular free flaps (34%-47%), 18,19 the present findings found that mandibular reconstruction did not escalate risk of ORN. The incidence of ORN in reconstructed mandibles was 7.9%, which was slightly lower than that of native mandibles (9.4%), and the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 96%
“…All patients underwent free flap surgery, with reconstructed mandibles defined by those who had fibular free flap, and native mandibles defined by those who had any non-osseous free tissue transfer. The overall incidence of Grade ≥2 ORN for the cohort was 9.0%, which is substantially lower than two studies specifically analyzing fibular flap reconstruction, 18,19 but consistent with those reported by other prior studies. 6,9,[24][25][26][27][28][29] The incidence of ORN between reconstructed and native mandible cohorts was not significantly different (7.9% vs. 9.4%, respectively).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Эффективность двухэтапной методики с установкой антимикробного спейсера при ППИ, обусловленной ТДЭ-возбудителями, по нашим данным и публикациям зарубежных авторов, крайне низкая, и операцией выбора в таких случаях может быть резекционная артропластика с несвободной пересадкой мышечного лоскута [6,7,8,9,10]. Несмотря на то, что уже продолжительное время радикальная хирургическая обработка с пересадкой мышечного лоскута, которая характеризуется высокой эффективностью в отношении купирования инфекционного процесса, является золотым стандартом лечения хронического остеомиелита любой локализации, применительно к тазобед ренному суставу (ТБС) данную методику используют крайне редко [11,12]. По-видимому, это обусловлено не только отсутствием у большинства ортопедов технических навыков и умения выполнить пластический этап операции, но и, как показывают немногочисленные публикации, прогнозируемо низким функциональным результатом резекционной артропластики [13,14,15].…”
Section: Introductionunclassified